News consumption patterns in Iceland - Jóhannsdóttir Valgerður (Nordicom Review)
News consumption has changed dramatically in the digital age, becoming increasingly complicated and fragmented. In this study, I analyse news consumption patterns in Iceland, drawing on data from a survey conducted in 2017, and compare it with news consumption in other Nordic countries. It is the first such study in Iceland in the digital age. The findings demonstrate that news are widely consumed by the general public, as in general in the Nordic region. Online sites are Icelanders’ most popular main source of news, followed by television and then social media. Legacy media are still most people's primary source of news, even if they are accessed on new platforms. Like in other Nordic countries, a small minority interacts with news online.